The Effect of Thoracic Radiotherapy on the Quality of Life in Lung Cancer Patients - (:unkn) unknown (CUREUS INC, 2021)
Introduction This study aimed to investigate changes in respiratory symptoms and quality of life (QoL) in patients with locally advanced and metastatic lung cancer receiving thoracic radiotherapy (RT). We investigated the correlation between the level of symptom relief and tumor response. Methods Thirty-two patients were included in this study. The European Organization for Research and Treatment of Cancer (EORTC) Quality of Life (QoL) Questionnaire (QLQ)-C30 and EORTC QLQ-LC13 were used to investigate QoL changes. Assessments were performed on the first day of RT, on the last day of RT, routinely monthly follow-ups, and three months after RT. Results The median age of the patients was 62; 88% of the patients were male. For the symptom scale, fatigue and dyspnea provided significant improvement at the end of RT (p=0.000, p=0.047). No significant improvement was observed at the end of RT in pain and insomnia. While coughing showed substantial improvement at the end of RT (p=0.004), the maximum improvement was achieved during the third-month follow-up (p<0.001). No significant improvement was observed at the end of RT in hemoptysis, but a considerable improvement was observed during the third-month follow-up (p=0.008). Conclusion This study confirms that RT offered palliation of respiratory symptoms and improved QoL in a substantial proportion of patients with lung cancer.
Keywords: radiotherapy; quality of life; lung cancer; QUESTIONNAIRE QLQ-C30; IMPACT; VALIDITY; CHEMOTHERAPY; RELIABILITY; VERSION